THE URBAN GEOHERITAGE OF CLERMONT-FERRAND: FROM INVENTORY TO MANAGEMENT - Vereb, Viktor; van Wyk de Vries, Benjamin; Guilbaud, Marie-Noëlle; Karátson, Dávid (Quaestiones Geographicae, 2020)
In sprawling urban areas, geoheritage is suppressed into limited niches. Potential geosites are highly vulnerable and could disappear completely during construction, or their integrity could be irreversibly modified. Here, we create an inventory of urban geoheritage for Clermont-Ferrand in France, recording more than 50 sites using the French national workflow. The results of the quantitative assessment have been used to differentiate between geosites (high scientific value) and geodiversity sites (limited scientific significance, important additional values). Finally, we discuss some important considerations on urban geoconservation, such as geotouristic itineraries or customized management strategies for each site and the whole city.